2008
DOI: 10.1213/ane.0b013e31818065bc
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double-Blinded Comparison of Phenylephrine and Ephedrine Infusion Combinations to Maintain Blood Pressure During Spinal Anesthesia for Cesarean Delivery: The Effects on Fetal Acid-Base Status and Hemodynamic Control

Abstract: When varying combinations of phenylephrine and ephedrine were given by infusion to maintain arterial blood pressure during spinal anesthesia for cesarean delivery, as the proportion of phenylephrine decreased and the proportion of ephedrine increased, hemodynamic control was reduced and fetal acid-base status was less favorable. Combinations of phenylephrine and ephedrine appear to have no advantage compared with phenylephrine alone when administered by infusion for the prevention of hypotension associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(60 citation statements)
references
References 16 publications
5
54
1
Order By: Relevance
“…Our findings are consistent with recent published data on management of maternal hypotension during spinal anesthesia [9][10][11][12][13][14][15][16][17][18] . Mercier FJ et al, 2007 16 analysed the different preventive and curative strategies for management of hypotension during spinal anaesthesia for cesarean section.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with recent published data on management of maternal hypotension during spinal anesthesia [9][10][11][12][13][14][15][16][17][18] . Mercier FJ et al, 2007 16 analysed the different preventive and curative strategies for management of hypotension during spinal anaesthesia for cesarean section.…”
Section: Resultssupporting
confidence: 93%
“…Fetal Parameters: Umbilical arterial (UA) pH and Umbilical venous (UV) pH was lower in group E. It was consistent with previous studies 4,11,12 . Depression of fetal pH and base excess with ephedrine has been postulated to be related to ephedrine induced stimulation of fetal metabolism 11 .…”
Section: Incidence Of Bradycardiasupporting
confidence: 91%
See 2 more Smart Citations
“…However, a number of studies have suggested ephedrine has a dose-related propensity to depress fetal pH and base excess (BE) in comparison to phenylephrine [3,4,5]. In addition, umbilical artery pH in a combination group of phenylephrine and ephedrine was lower than that of phenylephrine alone group [6,7]. When diverse combinations of phenylephrine and ephedrine were infused to maintain arterial blood pressure during spinal anesthesia for cesarean section, as the proportion of phenylephrine decreased and the proportion of ephedrine increased, decreases were observed in fetal pH, BE and umbilical arterial oxygen content [7].…”
Section: Introductionmentioning
confidence: 99%